Upaya Peningkatan Mutu Guru Melalui Pembimbingan Penyusunan Penelitian Tindakan Kelas di MIN 2 Kota Mataram - Teddy Rusdi (Jurnal Paedagogy, 2020)
The purpose of this study is to improve the quality of teachers through guiding the preparation of classroom action research in MIN 2, Mataram City. This research method uses school action research. This research was carried out by the principal as the main observer as well as a guide in the preparation of Classroom Action Research assisted by an administrative staff as an observer who recorded the results of the actions taken by the researcher. The action in this research was carried out in two cycles consisting of four meetings. The results of this study indicate that before holding the teacher evaluation results are very poor in understanding the material about proposals and reporting on classroom action research, after guidance in the first cycle there was an increase in grades that all teachers received below the standard value to 50% of teachers have obtained a standard value. After guidance in the second cycle, all teachers (100%) have the ability to prepare proposals and report on classroom action research. Thus in this school action research researchers consider to have been completed and have significant results.